Depression - Hammen, Constance L.; Watkins, Ed 1971- (Routledge/Taylor & Francis Group, 2018)
"Depression provides a valuable and accessible resource for students, practitioners, and researchers seeking an up-to-date overview and summary of research-based information about depression. With the help of clinical examples, the authors present chapters covering the hypothesized causes of depression, including genetic and biological factors, life stress, family, and interpersonal contributors to depression.The third edition extensively updates prior coverage to reflect advances in the field. The presumed causes of depression from both a biological perspective as well as from social and cognitive perspectives are explored in detail. Two chapters explore the most recent developments in pharmacological and biological interventions and in psychological treatments, as well as the prevention of depression. This new edition includes updated discussion about challenges in research, including heterogeneity and diagnosis of depression and proposed solutions, as well as the efficacy and availability of treatments.Authored by experts in the field who are active researchers and clinicians, Depression provides a state-of-the-art primer for final year undergraduate and postgraduate students, clinicians, professionals, and researchers seeking a broad reference task that critically evaluates research into depression." -- Provider by Amazon.